ChemInform Abstract: Magnetic and Magnetoresistive Properties of Thin Films Patterned by Self‐assembling Polystyrene Nanopheres. Issue 6 (11th February 2014) - Coisson, Marco; Celegato, Federica; Tiberto, Paola; Vinai, Franco; Boarino, Luca; De Leo, Natascia
Abstract Review: 41 refs.